Implementasi Kebijakan Pemutihan Pajak Kendaraan Bermotor Provinsi Bali - I Kadek Urip Wijaya; I Putu Dharmanu Yudartha; Komang Adi Sastra Wijaya (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the implementation of the motor vehicle tax amnesty policy (PKB) in Bali Province, as regulated by Bali Governor Regulation No. 24 of 2023. The policy is intended to alleviate the financial burden on the community by abolishing fines for late motor vehicle tax payments, while simultaneously increasing Local Original Revenue (PAD) and updating vehicle ownership data. This research employs a qualitative approach through interviews, observations, and documentation, and is based on the policy implementation model by Van Meter and Van Horn, which encompasses six variables: policy dimensions and objectives, resources, characteristics of the implementing agencies, inter-organizational communication, implementers' disposition, and economic, social, and political conditions. The findings indicate that the PKB amnesty policy has been implemented fairly well, supported by adequate human resources and technology, as well as effective coordination between the Bali Provincial Revenue Agency (BAPENDA), the Regional Technical Implementation Unit for Regional Revenue (UPTD PPRD), and other related agencies. However, several challenges remain, including congestion of queues at the end of the amnesty period, limited public access to information, and system disruptions caused by surges in online transactions. Despite these challenges, the policy is deemed successful in enhancing taxpayer compliance and providing tangible benefits to the community, particularly in reducing financial burdens. Recommendations include improved socialization, strengthening of the information technology system, and enhanced queue management to increase the policy's future effectiveness.